Legal Analysis of Inheritance Dispute Settlement Using a Mediation Approach - Nursam Prasetyo; Naya Amin Zaini; Wieke Dewi Suryandari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Inheritance disputes are a common legal issue in Indonesia and have the potential to lead to prolonged conflict among heirs. The process of resolving inheritance disputes through litigation is often time-consuming, expensive, and can damage family relationships. Therefore, mediation, as a form of alternative dispute resolution (ADR), is a more effective and efficient solution for resolving inheritance disputes. Mediation enables the parties to reach an agreement based on the principles of deliberation and consensus, thereby avoiding family breakdowns that often occur in the judicial process. This study aims to analyze the legal basis for resolving inheritance disputes through mediation, examine the effectiveness of the mediation approach in legal practice, and identify legal obstacles encountered in its implementation. The study employs a normative juridical method with an approach based on statutory regulations and legal doctrines related to inheritance dispute resolution and mediation. The various regulations that form the basis for this research include Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court, and provisions in inheritance law applicable in Indonesia, from the perspective of civil law, Islamic law, and customary law. Using a normative juridical approach, this research examines how mediation mechanisms can be effectively implemented in resolving inheritance disputes and examines various factors that can support or hinder their implementation. Therefore, this research is expected to contribute to developing a more equitable and expeditious inheritance dispute resolution system that maintains harmonious relationships between heirs.